Interações entre os Poderes Executivo e Legislativo no Processo Decisório: Avaliando Sucesso e Fracasso Presidencial - Simone Diniz (Universidade do Estado do Rio de Janeiro, 2005)
This article discusses how to evaluate success and failure in the approval of a given government agenda. Through an analysis of labor legislation reform bills submitted by the Brazilian Executive Branch from 1989 to 2001, the article shows that the success or failure of the Administration's agenda cannot be measured only by the bill's final review. The attempt was to demonstrate how submitting bills is part of a broader strategy, extending beyond the specific bill, and that passing bills is not necessarily the main objective of those submitting them.